Investigating the Effects of Electromagnetic Fields and Dimensions on the Electronic Properties of Gallium Arsenide Nanowire with Aluminum-Gallium Arsenide Coating in The Presence of Spin-Orbit Interaction - Alirteza Ghaffari (Journal of Optoelectronical Nanostructures)
Abstract In this research, the interaction of electromagnetic fields and sizes on the energy levels and specific functions of a GaAs nanowire coated with, along with the spin-orbit effect, has been carefully investigated. The magnetic field is applied in the direction parallel to the axis of the wire and the electric field is applied both in the plane perpendicular to the axis of the wire and in the direction parallel to it. To investigate the effects of the spin-orbit effect, in most cases, from the explicit form of the wave functions resulting from the solution of the Schrödinger equation Use related to the problem. We have shown that spin-orbit coupling together with external fields have a significant effect on the electronic properties of the wire. Since external magnetic field amplifies the intrinsic magnetic field, thus energy splitting due to SOI is bigger at higher B values. Because of the stronger role of magnetic field and weak effects of radial electric field on the SOI this phenomenon is not sensible when electric filed is radial.